Communities of faith and the global family planning movement: friends or foes? - Rebecca Oasa (Health for All Nations, 2017)
Within the Christian community, diverse views exist on the theological and moral dimensions of family planning, and specifically of contraception. Discussion of these issues frequently focuses on the family planning as a collection of methods and commodities used to space or limit pregnancies. Often missing from the discussion is the notion of family planning as a social and political movement, and the degree to which this movement's philosophy and goals are compatible with Christian theology. Nevertheless, faith-based aid organizations, including those with no objection to contraceptive use, must seriously grapple with the moral and practical implications of partnering with the institutions of the global family planning movement.